Intelligent virtual agents : 16th International Conference, IVA 2016, Los Angeles, CA, USA, September 20?23, 2016, proceedings /: 16th International Conference, IVA 2016, Los Angeles, CA, USA, September 20?23, 2016, proceedings. (2016) - Unknown
No abstract available